A classifying procedure for signaling turning points - Lasse Koskinen; Lars-Erik Öller (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
A Hidden Markov Model (HMM) is used to classify an out of sample observation vector into either of two regimes. This leads to a procedure for making probability forecasts for changes of regimes in a time series, i.e. for turning points. Instead o maximizing a likelihood, the model is estimated with respect to known past regimes. This makes it possible to perform feature extraction and estimation for different forecasting horizons. The inference aspect is emphasized by including a penalty for a wrong decision in the cost function. The method is tested by forecasting turning points in the Swedish and US economies, using leading data. Clear and early turning point signals are obtained, contrasting favourable with earlier HMM studies. Some theoretical arguments for this are given. Business Cycle ; Feature Extraction ; Hidden Markov Switching-Regime Model ; Leading Indicator ; Probability Forecast
Keywords: C22; C53; E37; 330